Dangerous Conversations in The Duchess of Malfi - John Gillies (Sillages Critiques)
The proposition of this essay is that conversation exists as a theme in its own right in The Duchess of Malfi. It is clear that Webster borrowed from The Civil Conversation (1586), as Steffano Guazzo’s book was known in English translation. As in Guazzo, honest conversation, in Webster's play, has a civil rather than courtly character, and as such the conversation theme corresponds with an antithesis that has been noted by John L. Selzer between merit and degree. But the conversation of Webster’s meritorious characters is entangled with dishonesty in ways that Guazzo would not have countenanced. The result is a moral ambiguity which is difficult to square with virtue ethics, and which calls for a reading in terms of the totalitarian contexts of the revenge play and the Tacitean history play then gaining ascendancy in Jacobean England. Ironically the Duchess is restored to her honesty by conversing with her murderer at the climax of the play.